Low frequency of mismatch repair deficiency in gallbladder cancer - Benjamin Goeppert; Stephanie Roessler; Marcus Renner; Moritz Loeffler; Stephan Singer; Melina Rausch; Thomas Albrecht; Arianeb Mehrabi; Monika Nadja Vogel; Anita Pathil; Elena Czink; Bruno Köhler; et al. (Diagnostic Pathology, 2019)
Abstract Background DNA mismatch repair (MMR) deficiency is a major pathway of genomic instability in cancer. It leads to the accumulation of numerous mutations predominantly at microsatellite sequences, a phenotype known as microsatellite instability (MSI). MSI tumors have a distinct clinical behavior and commonly respond well to immune checkpoint blockade, irrespective of their origin. Data about the prevalence of MSI among gallbladder cancer (GBC) have been conflicting. We here analyzed a well-characterized cohort of 69 Western-world GBCs. Methods We analyzed the mononucleotide MSI marker panel consisting of BAT25, BAT26, and CAT25 to determine the prevalence of MMR deficiency-induced MSI. Results MSI was detected in 1/69 (1.4%) of analyzed GBCs. The detected MSI GBC had a classical histomorphology, i.e. of acinar/tubular/glandular pancreatobiliary phenotype, and showed nuclear expression of all four MMR proteins MLH1, MSH2, MSH6, and PMS2. The MSI GBC patient showed a prolonged overall survival, despite having a high tumor stage at diagnosis. The patient had no known background or family history indicative of Lynch syndrome. Conclusions Even though the overall number of MSI tumors is low in GBC, the potentially therapeutic benefit of checkpoint blockade in the respective patients may justify MSI analysis of GBC.